Penatalaksanaan Fisioterapi Kasus Bronkitis Pada Anak Dengan Intervensi Chest Fisioterapi - Hanifia Dwi Hapsari; Fariz Ryan Maulana; Habil Mertageuna; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Bronchitis is a lower respiratory tract infection commonly experienced by children, particularly those under five years old. This condition leads to inflammation of the bronchi, increased mucus production, and airway obstruction. Young children often have difficulty clearing mucus effectively due to immature cough reflexes. One non-pharmacological therapy that can assist in mucus clearance and improve breathing is chest physiotherapy. Objective: To determine the effectiveness of chest physiotherapy in managing respiratory disturbances in children with bronchitis. Methods: This study was conducted through a literature review and observation of three pediatric cases diagnosed with acute bronchitis. Physiotherapy interventions were carried out over two days using techniques such as postural drainage, percussion (tapotement), and vibration, performed twice daily. Results: Following the interventions, all patients showed improvements in oxygen saturation, decreased respiratory rates, and a reduction in abnormal breath sounds such as crackles (ronchi) and wheezing. Overall, there was an increase in patient comfort, including better sleep quality and physical activity levels. Conclusion: Chest physiotherapy has proven effective in facilitating mucus clearance, improving lung ventilation, and accelerating the healing process in children with bronchitis.